A Case of Deep Vein thrombosis due to Protein C, Protein S Deficiency and Hyper-Homocystinaemia, A Rare Genetic Abnormalities - Hossain, Ahmed; Islam, Quazi Tarikul; Mitu, Umme Kulsum; Banik, Jayanta; Rahman, HM Mostafisur; Hasan, Mahmud; Mostafa, ABM Golam (Bangladesh Journal of Medicine, 2013)
Approximately 80% of Deep Vein Thromboses (DVTs) are clinically asymptomatic, 20% of those that actually demonstrate signs and symptoms. DVT associated with protein C and protein S deficiencies are rare genetic abnormalities that cause thrombophilia and lead to thrombosis. Here we describe a case of 55-year old male who presented with recurrent DVT of left lower limb and eventually diagnosed as a case of DVT due to protein C and protein S deficiency with hyperhomocystinaemia.. The particular interest in this case report is that it is important to consider sceening for thrombophilia incase of DVT with uncertain aetiology. DOI: http://dx.doi.org/10.3329/bjmed.v22i1.13598 Bangladesh J Medicine 2011; 22: 27-29